Stability of crop pollinator occurrence is influenced by bee community composition - Hutchinson, Louise A.; Oliver, Tom H.; Breeze, Tom D.; Greenwell, Matthew P.; Powney, Gary D.; Garratt, Michael P. D. (Frontiers in Sustainable Food Systems, 2022)
Bees provide a vital ecosystem service to agriculture by contributing to the pollination of the majority of leading global crops. Human well-being depends not only on the quantity of agricultural yields, but also on the stability and resilience of crop production. Yet a broad understanding of how the diversity and composition of pollinator communities may influence crop pollination service has previously been hindered by a scarcity of standardized data. We used outputs from Bayesian occupancy detection models to examine patterns in the inter-annual occupancy dynamics of the bee pollinator communities of four contrasting crops in Great Britain. We investigated to what extent pollinator community composition and species richness may affect the stability of crop pollinator occurrence. Across the four crops, we found that the inter-annual occupancy dynamics of the associated pollinator communities tended to be more similar in smaller communities with closely related pollinator species. Additionally, our results indicate that crop pollinator communities composed of a small number of closely related bee species show greater variance in mean occupancy compared to crops with more diverse pollinator communities. Finally, whilst our results initially indicated some redundancy within most crop pollinator communities, with no, or little, increase in the variance of overall mean occupancy when species were initially removed, this was followed by a rapid acceleration in the variance of crop pollinator occurrence as each crop’s bee pollinator community was increasingly depreciated. High inter-annual variations in pollinator populations have negative implications for crop production and food security. High bee diversity could ensure more stable and resilient crop pollination services, yet current agri-environment schemes predominantly benefit a limited suite of common species. Management may therefore benefit from targeting a wider diversity of solitary species in order to safeguard crop pollination service in the face of increasing environmental change.